Treatment Effect of Type 2 Diabetes Patients in Outpatient Department Based on Blockchain Electronic Mobile Medical App - Liu, Yang (J Healthc Eng, 2021)
As the pace of people's lives accelerates, there are more and more diabetic patients. This research mainly explores the treatment effect of type 2 diabetic patients based on blockchain electronic mobile medical app. Considering that it is more realistic to adopt an off-chain storage solution, the blockchain-based medical data sharing platform in this study adopts an off-chain storage solution. Only key information is stored in the blockchain network, and all medical data will be in the cloud space. For storage, cloud storage uses Aliyun's OSS storage service, which can be expanded infinitely. The cloud operation module is responsible for all operations that interact with cloud storage. The chain code can call the cloud operation module to upload the user's encrypted medical data and user ID to Alibaba Cloud's OSS. The chain code will return the storage address of the medical data and the authorized access address is sent to the blockchain network for consensus on the chain. The message processing module provides information processing functions such as chat information processing, APP use reminders, and health tips. The indicator recording module includes indicator recording functions including 6 indicators of blood sugar, medication, diet, weight, exercise, and sleep. The main function of the indicator analysis module is to display the curve trends of the 6 indicators recorded by the patient in three days, one week, and one month. Comparing the change range of the mean value of glycosylated hemoglobin at the beginning and end of the two groups of patients, it can be found that the change range of glycosylated hemoglobin in the intervention group is −6.04%, while the change range of the control group is only −3.26%. The impact of the mobile medical app designed in this study will indeed be reflected in the patient's blood sugar control and help patients to better control blood sugar.